A calibration methodology for light sources aimed at using immersive virtual reality game engine as a tool for lighting design in buildings. (1st May 2022) - Scorpio, Michelangelo; Laffi, Roberta; Teimoorzadeh, Ainoor; Ciampi, Giovanni; Masullo, Massimiliano; Sibilio, Sergio
Abstract: Immersive virtual reality represents one of the most promising technologic aids in the development of a functional lighting design, especially when considering different points of view as users' satisfaction. This paper presents a new methodology to use Unreal Engine 4.22 as a tool for lighting applications, allowing correct reproduction of artificial light distribution in the game engine by identifying and properly setting a restricted set of parameters. A real office was carefully reproduced, in both the Unreal Engine and DIALux evo software, as comparative case study. Then, the luminance distribution is calculated with both programs on the same surfaces in the virtual environment and compared with the real one. The results suggest a good reliability of the Unreal Engine in reproducing the light distribution, underlining slight differences under certain conditions. In light of these findings, the proposed method seems to validate the use of Unreal Engine as a light design tool. Highlights: Correct use of electric light in virtual reality from the photometric point of view. Measurements of luminance values within the Unreal Game Engine. Comparison of luminance values between Unreal Engine and DIALux Evo. Application of an electric light calibration methodology in a complex environment. With proper calibration, Unreal Engine can reproduce light distribution correctly.